Efek lingkungan kerja dan stres kerja terhadap kinerja karyawan melalui kepuasan kerja sebagai variabel intervening - Ade Fauji; Salsabila Damaihati (Jurnal Integrasi Sumber Daya Manusia, 2023)
One of the factors that influence the level of success of an organization is employee performance. This research was made to find out how the effect of work environment and work stress on employee performance through job satisfaction as an intervening variable at PT. Cilegon Fabricators. The research method used is correlational quantitative and the sample technique used is purposive sampling with 54 respondents. Data were obtained by distributing questionnaires and processing data using SmartPLS version 3.3.3. In this research it can be concluded that the work environment and work stress have an effect on employee performance, job satisfaction has no effect on employee performance, the work environment has no effect on job satisfaction, job stress has an effect on job satisfaction, and job satisfaction is not able to be an intervening variable in an unrelated relationship direct work environment and work stress on employee performance.